Konflik Sosial dalam Kumpulan Cerpen Tak Ada Asu di Antara Kita Karya Joko Pinurbo - Pranatha, I Dewa Dode Agus Adi; Triadnyani, I Gusti Ayu Agung Mas; Nama, I Ketut (Humanis; Vol 28 No 1 (2024), 2024)
This research discusses a collection of short stories entitled Tak Ada Asu di Antara Kita by Joko Pinurbo. This anthology contains fifteen short stories, five of which have the same conflict, namely the conflict between characters who work as authors. The five short stories are "Ayat Kopi", "Guru Bahagia", "Duel", "Korban Hoaks" and "Cakrawala". This research aims to answer the problem formulation, namely how social conflict is depicted in the short story collection Tak Ada Asu di Antara Kita by Joko Pinurbo. The five short stories were analyzed using social conflict theory. Analysis using social conflict theory aims to determine the conflict contained in this short story. The conflict found is a conflict between the author's characters. The analysis of social conflict in this short story is divided into three, namely forms of conflict, causes of conflict, and conflict resolution. The form of conflict is a description of the conflict that occurs in the author's characters. The cause of conflict is the thing that starts the conflict. Conflict resolution is the process or thing that causes the conflict to end.